Doing youth justice: analysing risk and need assessments in youth justice practice, 2004-2005 - Phoenix, Joanna (UK Data Service, 2009)
The past decade has seen a rapid expansion of the numbers of young people drawn into the criminal justice system and custody. This study investigates how youth justice practitioners (including Youth Offending Team (YOT) workers, solicitors, police and lay magistrates) assess the risks and needs of young law-breakers, and make decisions and recommendations. The study also explores how the young offenders themselves engage in these processes. A case study approach has been adopted where all individuals routinely involved in processing young law-breakers from a single small Local Authority have been interviewed. A sample of young offenders have also been interviewed. Six months of ethnographic observations of the youth court and YOT meetings and key policy meetings within the Magistrates’ Court, Local Authority and police authority were used to supplement interview materials. Currently, only the interview transcripts are available from the UKDA.